The Role of Principals in Implementing Inclusive Education Through Culturally Responsive School Leadership - Muhamad Tanzi; Hermanto Hermanto (AL-ISHLAH: Jurnal Pendidikan, 2024)
Inclusive education aims to ensure that all students can be fully involved, feel accepted, and feel valued. The principal must be willing to build an inclusive school in all aspects that respects the diversity of students in an assertive and supportive manner. This article's objective is to provide an understanding and description of the leadership role of principals to increase engagement and to establish an environment of acceptance for children with special needs in inclusive schools through Culturally Responsive School Leadership (CRSL) framework. The phases of a systematic literature review, which included designing a review, conducting a review, and assessing and documenting the outcomes of the review, were followed in the conduct of this study. Data were generated from reviewing 13 articles. This article reviewed articles published from 2018 to 2023 from the Taylor Francis, Science Direct, and Google Scholar databases. All articles are classified by year, internationally published articles, research articles, research objectives, and topics related to the role of inclusive school principals based on the CRSL framework. Purposive sampling was used to get the data, and specific search engine phrases were used. After gathering the data, content analysis methods were used to examine it. This study discovered that the principal's leadership is essential for developing inclusive educational management. Principals need to be responsive and serious about the diversity of students with special needs, which includes reflection on leadership, developing responsive teacher abilities, and building an environment that is inclusive of children with special needs.